2015
DOI: 10.1111/1751-7915.12316
|View full text |Cite
|
Sign up to set email alerts
|

A novel bacteriophage cocktail reduces and disperses Pseudomonas aeruginosa biofilms under static and flow conditions

Abstract: Summary P seudomonas aeruginosa is an opportunistic human pathogen that forms highly stable communities – biofilms, which contribute to the establishment and maintenance of infections. The biofilm state and intrinsic/acquired bacterial resistance mechanisms contribute to resistance/tolerance to antibiotics that is frequently observed in P . aeruginosa isolates. Here we describe the isolation and characterization of six novel lytic bacteriophages: viruses that infect bacteria, which together efficiently infect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 60 publications
(70 reference statements)
4
64
0
3
Order By: Relevance
“…evaluated the safety and efficacy of a bacteriophage cocktail (BFC-1, including PhiKMV-like phages) in the treatment of burn wound infections in a controlled clinical trial, and BFC-1 is active against the P. aeruginosa and Staphylococcus aureus strains in their model 41 . Alves’ studies suggest that the use of phage cocktails (including one phiKMV-like phage DL62) against P. aeruginosa could provide practical alternatives to antibiotic treatments for combating biofilm-related infections and in particular the devastating effects of biofilm-related CF infections 42 . Hence, further knowledge of the gene products of PhiKMV-like phages and their targets in bacteria are also extremely significant and helpful in antibacterial agent discovery and identifying potential toxic genes.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the safety and efficacy of a bacteriophage cocktail (BFC-1, including PhiKMV-like phages) in the treatment of burn wound infections in a controlled clinical trial, and BFC-1 is active against the P. aeruginosa and Staphylococcus aureus strains in their model 41 . Alves’ studies suggest that the use of phage cocktails (including one phiKMV-like phage DL62) against P. aeruginosa could provide practical alternatives to antibiotic treatments for combating biofilm-related infections and in particular the devastating effects of biofilm-related CF infections 42 . Hence, further knowledge of the gene products of PhiKMV-like phages and their targets in bacteria are also extremely significant and helpful in antibacterial agent discovery and identifying potential toxic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Planktonic and biofilm C. amycolatum culture and preparation of the planktonic-conditioned media (PCM) and the biofilm-conditioned media (BCM). The strains were initially assessed for the biofilm production using the assay with crystal violet that was carried out as previously described (Alves et al 2016) with some modifications. The assay was performed in the 96-well microtiter plates (NUNC, Thermo Fisher Scientific Inc, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that phages are currently considered as promising antimicrobial agents for biofilm prevention and control [7,8]. Nonetheless, although several studies have reported significant reductions in mono and dual-species biofilms after phage treatment [2,3,[9][10][11][12], the complete eradication of biofilms is an almost impossible task [13 ]. Phages need to reach their host bacteria and attach to specific receptors located at cell surfaces before infection and replication inside their hosts is initiated.…”
Section: Limitations Of Bacteriophages When Used As Anti-biofilm Agentsmentioning
confidence: 99%
“…Multiple phages with different host ranges and targeting different receptors can be combined in a single phage preparation (phage cocktails) to expand their spectrum of activity and prevent the development of phage-resistant bacterial variants [70]. Several studies have reported the use of this strategy to treat bacterial biofilms [2,10,11,51,71]. For example, Fu et al studied the prevention of P. aeruginosa biofilm formation on hydrogelcoated catheters pre-treated with phages [10].…”
Section: Phage Cocktailsmentioning
confidence: 99%